Eclipsing Atlantis: Trans‐Atlantic Multilateralism in Trade and Monetary Affairs as a Pre‐History to the Genesis of Social Market Europe (1942–1950)*. (7th December 2018) - Segers, Mathieu
Abstract: The common understanding of the history of European integration obfuscates much of the strong bonds between European integration and its pre‐history in western multilateral co‐operation This western co‐operation centred around the inter‐connected policy fields of monetary management, trade and social policies during the pre‐phase of European integration. This contribution reconstructs the trans‐Atlantic institutional framework, within which a unique multilateralism in post‐war Western Europe, could emerge. The analysis suggests new explanations for the specific design, which characterizes this European variant of post‐war multilateralism: a regionally oriented 'social market' pursued through a process of European integration.